Comparison of the protective effects of various antiulcer agents alone or in combination on indomethacin-induced gastric ulcers in rats - OKUYAN, BETÜL; SANCAR, MESUT; RABUŞ, ŞULE (ELSEVIER GMBH, 2012)
The aim of this study which was structured with the objective of determination of the optimum protective therapy against the long term NSAID therapy-induced ulcers was to compare the gastro-protective effects of various antiulcer drugs (ranitidine, omeprazole, bismuth and misoprostol)alone or in combination with each other in different doses on indomethacin-induced gastric ulcers in rats. In this experimental study the protective effect of misoprostol (100 mu g/kg/day and 10 mu g/kg/day i.g.), omeprazole (5 mg/kg/day and 1.5 mg/kg/day i.p.), ranitidine (40 mg/kg/day and 10 mg/kg/day i.p.), bismuth (70 mg/kg/day and 15 mg/kg/day i.g.), combinations of misoprostol (10 mu g/kg/day i.g.) plus omeprazole (1.5 mg/kg/day i.p.) and misoprostol (10 mu g/kg/day i.g.) plus ranitidine (10 mg/kg/day i.p.) are investigated on indomethacin (50 mg/kg/day s.c.) induced gastric ulcers. Half an hour before indomethacin administration, each group received the above treatment regimens for 5 days. After 5-day treatment, the rats were sacrificed and histopathological and hematological examinations were performed. The following regimens were found to be effective in the prevention of indomethacin-induced gastric lesions: 100 mu g/kg misoprostol, 10 mu g/kg misoprostol, 5 mg/kg omeprazole, combination of 10 mu g/kg misoprostol plus 1.5 mg/kg omeprazole and 10 mu g/kg misoprostol plus 10 mg/kg ranitidine. The prevention rates achieved by these treatments were 71.4%, 50%, 47.6%, 52.4% and 50%, respectively. As a result of this study, misoprostol and omeprazol were found to be effective in protection against NSAID-induced gastric problems: while, ranitidine and bismuth were not. Also, the combinations of these agents were not found to have additive or synergistic effects. (C) 2010 Elsevier GmbH. All rights reserved.
Keywords: Indomethacin-induced gastric ulcer; Omeprazole; Misoprostol; Ranitidine; Bismuth; Rat; NONSTEROIDAL ANTIINFLAMMATORY DRUGS; OMEPRAZOLE; MISOPROSTOL; PREVENTION; CIMETIDINE; SUCRALFATE; ASPIRIN; THERAPY